Receptivity of the mandible versus the maxilla to external stimuli in patients with complete dentures. Issue 3 (July 2019) - Kimoto, Suguru; Furuse, Nobuhiko; Ogawa, Takahiro; Nakashima, Yoshio; Furokawa, So; Okubo, Masakazu; Yamaguchi, Hidenori; Kawai, Yasuhiko
Abstract: Purpose: This study aimed to investigate whether the mandible is more receptive to external stimuli than the maxilla in patients with complete dentures by comparing regional current perception thresholds (CPTs) and pain threshold (PTs). Methods: A single operator obtained measurements from maxillae at the incisor foramen and the left side of the greater palatine foramen region and the mandible at the left side of the mental foramen region, using the Neurometer CPT/C device, CPT and PT values from the oral mucosa of 20 edentulous individuals wearing complete dentures were analyzed. Participant characteristics such as mucosal thickness, occlusal force, age, and sex. Mucosal thickness over target regions and occlusal force were measured by the same operator using Krupp SDM and Occlusal Force-Meter GM10s devices. Differences in CPT and PT among the three measurement regions were tested with an analysis of covariance, and post hoc t-tests with the Bonferroni correction. Results: There were no significant differences between the mental foramen, incisor papilla, and greater palatine regions CPT values. PTs obtained at all current frequencies (2000 Hz, 250 Hz, and 5 Hz) were lowest in the mental foramen region and highest in the greater palatine region. Covariates including sex, mucosal thickness, and occlusal force had no significant influence on CPT or PT values at all frequencies. Conclusions: The mandible exhibits higher receptivity to external pain stimuli than the maxilla.